2004
DOI: 10.1177/0002764204266238
|View full text |Cite
|
Sign up to set email alerts
|

Breaking the Ethnographer’s Frames

Abstract: This article assesses the use of auto-driven photo elicitation among children Buddhist monks in Sri Lanka. Comparing the data previously collected from word-only interviews with the data collected from auto-driven photo-elicited interviews, the author discusses how the latter field method tended to evoke greater descriptions from the research participants, how the descriptions were more emotionally charged than word-only descriptions, and how the autodriven approach was an effective means of bridging the cultu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(55 citation statements)
references
References 9 publications
0
53
0
2
Order By: Relevance
“…On the one hand, from the researcher to the interviewee, by showing images and subsequently (2000) refers to the value of kin pictures for the family collective memoir in a similar methodological way to Christian (2012) alluding to the relevance of images for the study of collective religious experiences. Likewise, the family album becomes a medullar device for life stories and the past-present reinterpretation of biographies (Naguib 2008), as well as the study of emotional responses to research enquiries (Samuels 2004), the provision of evidence for theory (Twine 2006) or self-representation strategies (Vivienne and Burguess 2013), among other fields.…”
Section: Pictures Collections and Family Albumsmentioning
confidence: 99%
“…On the one hand, from the researcher to the interviewee, by showing images and subsequently (2000) refers to the value of kin pictures for the family collective memoir in a similar methodological way to Christian (2012) alluding to the relevance of images for the study of collective religious experiences. Likewise, the family album becomes a medullar device for life stories and the past-present reinterpretation of biographies (Naguib 2008), as well as the study of emotional responses to research enquiries (Samuels 2004), the provision of evidence for theory (Twine 2006) or self-representation strategies (Vivienne and Burguess 2013), among other fields.…”
Section: Pictures Collections and Family Albumsmentioning
confidence: 99%
“…A PET não apenas proporciona mais informações do que as entrevistas puramente verbais, como também propicia acesso a informações diferentes (SAMUELS, 2004). Por exemplo, no contexto de pesquisas de marketing, pedir a potenciais consumidores para lembrarem as suas atitudes ou crenças acerca da utilização de um produto, sem nenhum estímulo visual, é muito diferente do que lhes mostrar uma imagem de um cenário com o produto em uso.…”
Section: Photo Elicitation Techniqueunclassified
“…Photographs sharpen the memory and provide "external" stimuli, and attention is moved away from the faces of the participants to the photographs, which may reduce stress in the interview situation. Samuels (2004) argues that one can expect richer descriptions, grounded in the interviewees' own lived and affective experiences, rather than a simple listing of abstract qualities from such a method. Collier & Collier (1967) also showed that visual stimuli could act as a reminder of impressions gained from other senses.…”
Section: The Visual Dimensionmentioning
confidence: 99%
“…Participants are allowed to present their own worlds, which increases the chance of obtaining an insider perspective and discovering new and different patterns which might erase the researcher's own preconceptions (Samuels, 2004). There are many motivations to use pictures when studying image, but they are rarely used in studies of retail store image.…”
Section: The Visual Dimensionmentioning
confidence: 99%